The ASEAN market: cross-border collaboration in Islamic finance between Malaysia and Thailand - Yussof, Sheila Ainon; Haron, Razali (2017)
Islamic finance offered a viable and moral-ethical alternative when the world economy was suffering from the global financial crises due to high debt-gearing and excessive speculations leading to liquidations and losses. In the casino-like scenario of the conventional order, Islamic finance is viewed as a game-changer, setting new rules and behavioral patterns that appeal to humanity and other civilizations due to its adherence to the universal principles of justice, equity and good conscience. In the beginning, Islamic finance may have started off with a nationalistic or religious fervor due to independence from colonialism and reassertion of an Islamic identity. But later it became evident to the world that its core principles, if implemented sincerely, can prevent exploitation, monopoly, bribery and corruption, excessive spending and hoarding of wealth, high debt-gearing and speculation. Ideally, Islamic finance should be promoting values such as entrepreneurship, transparent dealings, risk sharing. and profit and loss sharing rather than a predetermined return. Islamic finance is also based on ethical principles such as trustworthiness and honest dealings, sanctity of contracts, moderate and pragmatic behavior and equitable treatment of stakeholders This paper will examine the role of Islamic finance in developing the ASEAN market through cross-border collaboration, specifically with Thailand, through three engines of growth: the Sukuk market, Halal market and Waqf. Islamic finance has opened up many opportunities to the minority Muslims in Thailand and helped speed up the integration process. As the world becomes smaller and cross-border players increase, there is a need to have greater legal and regulatory certainty. To ensure Islamic finance is on a level playing field with conventional finance as it crosses borders, the present authors recommend a mutual relaxation of taxation laws and a trade liberalization policy. Lastly, a unified and concerted effort is needed to promote equitable development of ASEAN member nations within the Islamic framework of “prospering thy neighbours”.